The pursuit of difference: Jennifer Pharr Davis' memoir Called Again, A Story of Love and Triumph. Issue 3 (2nd September 2018) - Abdelmotagally, Noha F.
ABSTRACT: The concepts associated with sameness and difference are mostly laboratory-based and inefficient for handling the complexities associated with cultural ideology and social hierarchy. Women athletes' memoirs that create a writer-reader pact and reflect on a real-life experience can prove valuable for examining the different concepts of sameness and difference. To impose a reconsideration of these two concepts, the psychologists C. R. Snyder and Howard L. Fromkin's theory of uniqueness will be braided with Jennifer Pharr Davis' memoir, Called Again (2013). I find it challenging to research an under-researched subject (Jennifer Pharr Davis) and field of study (extreme women trail hikers). The choice is set on Davis' memoir because: 1) women are socially accused of deviation and nonconformity, 2) women's memoirs are believed to be more confessional than men's, and 3) Called Again traces three pursuits of difference while hiking the Appalachian Trail, which better serves the purpose of the study.